Imaging of a small bowel cavernous hemangioma: report of a case with emphasis on the use of computed tomography and enteroclysis - Corsi, A.; Ingegnoli, A.; Abelli, et al., P. (Acta Biomedica Atenei Parmensis, 2007)
Hemangiomas of the small bowel are rare benign tumors, that are dangerous since they may cause massive or occult gastrointestinal bleeding.We describe a case of a jejunum cavernous hemangioma detected by computed tomography (CT) and barium studies. An abdominal CT scan (with intravenous contrast agent) depicted a pronounced contrast enhanced lesion arising from the front wall of a loop of the proximal ileum. Enteroclysis revealed a small intramural nodular defect.